Raskin Subsidized Rice Delivery - World Bank (World Bank, Jakarta, 2017)
The Beras untuk Rakyat Miskin (Raskin) program was introduced as an emergency food security program in 1998; it delivers rice to be purchased at subsidized prices, prioritized to poor and near-poor households. In terms of government expenditure, Raskin remains the largest permanent social assistance transfer targeted to poor households in Indonesia. Though developed as a response to crisis, Raskin has become a permanent program and in real expenditure terms is one of the few social assistance programs with a larger budget in 2010 than in 2005. In 2010 Raskin accounted for nearly 53 percent of all household-targeted social assistance spending carried out by the central government. Over 2000 to 2010, the amount of rice allocated by the Raskin program has averaged over 2 million tons per year; in 2010 the almost 3 million tons allocated could have delivered between 30 and 40 kilograms per month to the approximately 6.2 million households at or below the poverty line. The distribution of Raskin rice does not closely align with the objectives laid out in program manuals and official documentation for at least three reasons. First, not all of the rice procured for the Raskin program makes it to households. In the three most recent years for which there is audited budget data (2007 through 2009), nationally representative household surveys indicate that only half (or less) of the rice procured for Raskin is purchased by households. The readily-available budget and administrative records cannot indicate where the bulk of this "missing" rice exits the delivery chain, and no single agency or authority is in charge of Raskin rice from procurement to household purchase. This note assesses the operation and implementation of the Raskin program to determine how well poor households are served by the program and the overall cost of program resources. The note provides quantitative analysis of the coverage, incidence, and average benefit levels of Raskin to determine both the progressivity of the program's targeting and the adequacy of benefit levels. Qualitative information on program delivery and program operations will also shed light on areas for reform. An evidence-based appraisal of the household-based transfer currently consuming over 50 percent of the entire social assistance budget envelope can provide inputs to the Government of Indonesia (GOI) as it continues to try to achieve both Pro-Poor development for all Indonesians and the Millennium Development Goals (MDGs).